The protective effect of Lonicera japonica polysaccharide on mice with depression by inhibiting NLRP3 inflammasome - Liu, Ping (Ann Transl Med, 2019)
BACKGROUND: Depression is associated with the abnormal activation of the human inflammatory response system, which is a life-threatening disorder affecting millions of people of all ages around the world. The purposes of the present study were to examine the effect of Lonicera japonica polysaccharide (LJP), a polysaccharide extracted from Lonicera japonica Thunb., on depressed mice treated with the unpredictable emotional stress stimulation. METHODS: The components of LJP after extraction were detected by HPLC. Depression model is established through chronic unpredictable stimulation, and the depression behavior was assessed by mouse behavioral assessment, including open field, elevated plus maze, tail suspension, forced swim. Pathological changes in hippocampus of mice were observed by HE and toluidine blue staining. Protein expression of NLRP3 inflammasome pathway was detected by WB. RESULTS: It was showed that LJP mainly consisted of 8.7% GalA, 8.2% Rha, 16.2% Gal, 19.5% Ara, 26.9% Glc and 20.5% Man, with the average molecular weight approximately ranging from 1 to 1,000 kDa, which could significantly reduce the time in the open arms and the immobility time of the depressed mice in behavioral tests, and the expressions of NLRP3, IL-1β, and caspase-1 in the hippocampus of depressed mice were significantly upregulated. CONCLUSIONS: LJP exhibited a strong protective effect on mice with depression by inhibiting NLRP3 inflammasome. The results will help to understand the potential use of Lonicera japonica Thun polysaccharide in pharmaceutical and food applications better.